Some economics of private digital currency - Joshua S. Gans; Hanna Halaburda (Bank of Canada, 2013)
This paper reviews some recent developments in digital currency, focusing on platform-sponsored currencies such as Facebook Credits. In a model of platform management, we find that it will not likely be profitable for such currencies to expand to become fully convertible competitors to state-sponsored currencies.
Keywords: D42; E4; L51; 330; Bank notes; Economic models; Payment clearing and settlement systems